Faktor-faktor Yang Memengaruhi Indeks Pembangunan Gender di Indonesia Tahun 2020 - Surhaliza Aprilianti; Yaya Setiadi (Politeknik Statistika STIS, 2022)
One of the capital in development is human resources. Human development is often related to gender differences which discuss how to achieve gender equality in order to improve human resources without discriminating between men and women. Men and women are equally important to be considered in order to contribute to achieving full human development. Based on BPS data, there is a gap in human development outcomes based on gender as measured by the Gender Development Index (GIP) and the IPG achievement in 2020 has not met the targets of the Strategic Plan of the Ministry of Women's Empowerment and Child Protection and there are still many provincial GPIs that are below the national GPI. The purpose of this study is to determine the factors that influence Indonesia's GPI in 2020 using multiple linear regression analysis. The results of this study show that female TPT and sex ratio have a significant effect on Indonesia's IPG in 2020, while female APS 16-18 years and the percentage of women who experience health complaints have no significant effect on Indonesia's IPG in 2020.